Perancangan Skin Outfit Minangkabau Pada Game PUBG Mobile Sebagai Bentuk Promosi Konten Lokal Minangkabau - Hafizatul Ismi; Dwi Mutia Sari (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2023)
Minangkabau has a variety of cultures, starting from clothing, architecture, motifs, beliefs, songs, and visual characters. One of the uniqueness of Minangkabau is that it has traditional clothing that is its own characteristic. One of the famous traditional clothes in Minangkabau is Bundo Kanduang clothing. Skins have various types, one of which is Skin outfit which is a skin for characters in the game. This Minangkabau skin outfit is designed for the PUBG mobile game or known as Player Uknown's Battleground mobile. The delivery in designing this skin outfit uses the main media Manual Book. Manual book that contains history, making skin outfits, skin items and supporting media, namely T-shirts, posters, stickers, x banners, totebags, hangers / merchandise and Instagram social media to promote. The compounding method used is Glassbox with a 5w + 1h data analysis method, namely what, who, when, where, why, and how. With the completion of this Manual Book, it is hoped that it can become a media that has effective and communicative information for the target audience.